2007
DOI: 10.1007/s11745-006-3008-2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Dietary Cholesterol Oxidation Products and Their Downstream Metabolic Effects Are Reduced by Dietary Apple Polyphenols

Abstract: Exogenous and endogenous cholesterol oxidation products (COPs) perturb various metabolic processes, and thereby they may induce various homeostasis-related disorders. Here, we observed that procyanidin-rich dietary apple polyphenol (APP) from unripe apples alleviates the perturbation of lipid metabolism by decreasing the exogenous COP levels in rats. Dietary COPs may be the greatest source of COPs found in the human body. Rats (4 weeks of age) were fed AIN-purified diets containing 0.3% COPs supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
5
31
0
Order By: Relevance
“…Some of these compounds may be absorbed from the intestine and their metabolites may influence lipid metabolism (OGINO et al, 2007).…”
Section: Vitamin C/phenolic Compounds/tanninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds may be absorbed from the intestine and their metabolites may influence lipid metabolism (OGINO et al, 2007).…”
Section: Vitamin C/phenolic Compounds/tanninsmentioning
confidence: 99%
“…However, there are not many researches studying the use of apples in this area, and some of them include their antioxidant compounds (APRIKIAN, et al, 2003;BOYER;LIU, 2004;LEJA;MARECZEK;BEN, 2003;LEONTOWICZ et al, 2001;LEONTOWICZ et al, 2003;OGINO et al, 2007;SEMBRIES et al, 2006;VIDAL et al, 2005).…”
mentioning
confidence: 99%
“…HPs inhibited the activity of a pancreatic lipase in our in vitro experiment the half maximal inhibitory concentration IC 50 of HPs was 2.5 mg/ ml . Dietary apple polyphenols, especially high-molecularweight procyanidins, may inhibit the intestinal absorption of lipids through micellar disruption 38 . The excreted feces level in the H-group was the highest among the 2 study groups NC-group: 2.75 0.11 g/day; C-group: 2.86 0.06 g/ day; H-group: 3.19 0.05 g/day .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an in vitro test has demonstrated that they have an inhibitory effect on pancreatic lipase activity and on the micellar solubilization of fat 13 . Moreover, several studies involving animal experiments have revealed that the quantity of fatty acids excreted in rat feces increased with the rat s intake of apple polyphenols 14 , that apple polyphenols had an inhibitory effect on triglyceride absorption in mice 15 in a triglyceride loading test conducted on mice, and that apple polyphenols had a reducing effect on abdominal visceral fat 16 .…”
Section: Introductionmentioning
confidence: 99%